Pengembangan Permainan Tradisional Gotri untuk Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun di Paud Melati Desa Nyurlembang Kecamatan Narmada Tahun 2021 - Rara Aulia Putri; Baik Nilawati Astini; Nurhasanah Nurhasanah; Ika Rachmayani (Indonesian Publication Center, 2021)
This study aims to develop the traditional game of Gotri in improving gross motor skills of children aged 5-6 years at PAUD Melati, Nyurlembang Village, Narmada District in 2021. This type of research uses R&D development with 3 stages of development consisting of planning, implementation, and evaluation/reflection. The subjects of this study were 10 children aged 5-6 years. The research method used was observation and documentation. Data analysis used descriptive qualitative analysis. This study can develop children's gross motor skills through traditional buckshot games with the following steps: (1) Preparing tools and materials to be used in the buckshot game such as used bottles, small balls and cardboard (2) Before starting the playing activities the teacher invites children to warm up ( 3) Make an agreement to play in the game of buckshot (4) Players line up without scrambling outside the game track (5) Players are given a signal first then run in a zig zag (6) Player rolls a small ball (kasti) from a distance of 1 meter (7) Players roll a small ball towards the target in a bent position (8) Players run to pick up a small ball (colored ball) then put the ball into a cardboard box from a distance of 1 meter. The results showed that the steps of playing buckshot in this study can improve children's gross motor skills, it can be seen in the development stage I reached a percentage of 45.87%, while in the second development stage it increased by 61.90%, and at the development stage III has increased optimally with a percentage of 79.70%. Based on the results of this study, it can be concluded that the traditional game of gotri can improve gross motor skills of children aged 5-6 years at Melati PAUD, Nyurlembang Village, Narmada District in 2021.